MODEL PENDAYAGUNAAN SUMBERDAYA PANGAN LOKAL UNTUK MENINGKATKAN NILAI TAMBAH (Studi di Kecamatan Wonoboyo Kabupaten Temanggung) - Sriyanto Sriyanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
Food is an essential human need. Local food resources, as variations in food consumption society, has been displaced by the food pattern of rice and wheat. This challenge, which requires innovation and transformation of the physical form of local food to be liked by the community and value-added food technology process. This study describes the management of the local food chain from upstream - downstream. The result, that the number of farms in Temanggung Regency, declined 9,05% during 2003-2013. Influence on output, the decline in cattle population is 33,59%. The potential of local food resources are corn, potatoes and cassava. Marketing, slash sold at harvest, because of the practical. A small portion is used as a raw material by the snack food industry domestic industry. Type snack food industry locally grown is cassava chips (most, 17 locations), and a banana chips / taro chips. Marketing is done by a small proportion of women farmer group members, which is deposited on the stalls / shops, restaurants and outlets instistusi cooperative government. Promotion is done through exhibitions in various cities. Models utilization of local food resources, can not be separated from the role of chairman of the entrepreneurial group. While members of the group as a support in the production and marketing process. Value chain and the policies that need to be prepared : the provision of quality seeds of local food as a source of raw materials by agricultural institutions, food processing technology by industry and academia, capital by cooperatives, promotion and marketing by the field of trade.